The ß-catenin/CBP-antagonist ICG-001 inhibits pediatric glioma tumorigenicity in a Wnt-independent manner - Schlagmann, Maria; Pfister, Stefan (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.15934 Maria Wiese, Neele Walther, Christopher Diederichs, Fabian Schill, Sebastian Monecke, Gabriela Salinas, Dominik Sturm, Stefan M. Pfister, Ralf Dressel,...